BROADENING ACCESS; AN INTEGRATED SPECIALIST NURSE LED PALLIATIVE CARE CLINIC WITHIN A GENERAL PRACTICE SETTING. Issue 1 (1st March 2013) - Harrop, E; Baillie, J; Byrne, A; Stephens, K; Nelson, A
Abstract : Introduction: A community nurse-led palliative care clinic was introduced at a large GP practice in April 2012. This is a new model for engaging patients and GPs with potential for broadening access to palliative care services. Previously clinical nurse specialists (CNS) supported patients by home visits, with the fortnightly clinic introduced as a complementary resource to consolidate the joint primary/ palliative care approach. Aims and Methods: This study evaluates: ▸ Implementation processes ▸ The impacts of the clinic on patient experiences and professional practices, ▸ The uptake of palliative services ▸ The management and delivery of palliative care by GPs and CNS. Baseline interviews with GPs (n=5) and CNS (n=4) were undertaken in February 2012. Patient interviews (n=6–12) and follow-up interviews with GPs (n=6–10) and CNS (n=4–6) are planned for January 2013. Patient interviews will be analysed using Interpretive Phenomenological Analysis methodology, interviews with health professionals will be analysed using Framework Analysis. The evaluation will also report on quantitative data from the palliative care register and patient tracking. Results: Baseline interview data highlight the need for improved referral and communication practices, especially for non-cancer patients. Aspirations for the clinic included: earlier referral; improved communication and continuity of care; psychological and practical benefits for patients/ carers and more targeted use of specialist nursing resources. Data from patient and follow-up interviews will be reported against these aims, with additional themes identified. Conclusions: Conclusions will be drawn on the effectiveness of the clinic and implications identified for palliative care provision in primary care settings, including the potential of such models to broaden access to palliative care.